Changes In Body Weight, Body Mass Index, Vo2max, Agility and Speed After Implementing Tuja Shuttle Run Training For 6 Weeks - Nimas Nur Azizah, Tutur Jatmiko, Kunjung Ashadi, Tri Setyo Utami,Fatih Hazar, Sunanto, Heni Yuli Han (Journal of Educational Studies, 2025)
Fencing is a very physically demanding activity that calls for quick reflexes, quick thinking, and both aerobic and anaerobic endurance. Consequently, in order to improve the physical performance of athletes, a suitable training regimen is required. Tuja Shuttle Run and other forms of High Intensity Interval Training (HIIT) are one possible method of training. The purpose of this research was to analyse the effects of a six-week training program called the Tuja Shuttle Run on fencing competitors' weight, BMI, VO?Max, agility, and speed. Using a non-randomized pretest-posttest design, this study adopted a quasi-experimental approach. Twelve male fencers from Magetan Regency, ranging in age from sixteen to nineteen, were there to get ready for the East Java Provincial Sports Week (Porprov). We measured body weight and height to get BMI, ran a 20-meter dash to find speed, estimated VO?Max using a Multi-Stage Fitness Test (MFT), and evaluated agility with a T-Test. A six-week high-intensity interval training regimen was used for the Tuja Shuttle Run. A paired sample t-test was used to analyse the data, and a significance threshold of 0.05 was set. Several measures, including body mass index (BMI) (p = 0.031), speed (p = 0.000), VO?Max (p = 0.000), and agility (p = 0.000), showed statistically significant variations between the pre- and post-test results. These findings provide credence to the idea that fencing athletes might benefit from the Tuja Shuttle Run training approach by enhancing many aspects of their physical condition. So, this training paradigm may be seen as a different way to help athletes improve their physical performance, especially in regards to their body mass index (BMI), maximal oxygen consumption (VO?), agility, and speed.